Diálogo social e neoliberalismo : análise comparativa dos conselhos econômicos e sociais da Espanha, de Portugal e do Brasil (1991-2016) - Carneiro, André Pereira (2016)
The neoliberal ideology has manifested prevalent after the crisis experienced from the end of the 70’s, with its defense of the need to reduce the state apparatus and of the expansion of freedom of the economic agents, which interfered in the model of the democracy. From the perspective of this ideology, the hegemonic model of democracy was reinforced, giving prevalence to the representative system, as well as consolidating the purely procedural matter, linked only to the universal suffrage and without the moral perspective of change in society. This has increased inequality and strengthened the influence of the market and external stakeholders on public policy. Therefore, democracy was affected with the growth of social apathy and questions about the politic, since the alternation of projects does not exist. In order to mitigate these problems, increasing social participation would be the instrument and this was defended even by multilateral agencies such as the ILO, to bring social dialogue as one of its strategic objectives. The social dialogue would be used to broaden the discussion of economic and social policies, enabling the construction of alternatives and concerted solutions. Within this context of domination of neoliberal ideology, it has been seen the creation of Economic and Social Councils in Spain, Portugal and Brazil. In Spain and Portugal, the creation occurred at a time when they were needed to do major reforms to adapt these countries to the dictates of the European Union, especially given the proximity of the monetary union. In Brazil, the creation was presented as a tool to counter to that ideological predominance and it was placed, as one of its functions, the construction of a new social pact. Considering this reality, the study aims to analyze if the social dialogue institutionalized in the Economic and Social Councils of these countries actually served as an instrument for a greater social participation and for the creation of concerted alternatives for economic and social development. The hypothesis to be worked is that the practice of these Councils in Spain, Portugal and Brazil is similar, in order to give legitimacy to economic and social policies or the government, despite the difference of speech in their creation. To enable this study, the second chapter provides the linkage of democracy to capitalism, especially during the period of ideological domination of neoliberalism. The third chapter makes a historical overview from the democratization process until the creation of the Councils. In the fourth, the institutional characteristics and evolution of the social dialogue with the creation of the Councils are showed. To display this evolution, it was used articles about the social dialogue in those countries and primary documentation provided by each of the Councils, that being the opinions made by the plenary of the Councils of Spain and Portugal and the minutes and speeches of the regular meetings of the Council of Brazil. In the fifth chapter, it is singled out problems seen in the process of the institutionalized social participation. After that, it is presented the conclusion that the institutionalization of social dialogue was not used to the democratic expansion as thought.